PENGEMASAN VAKUM CABAI RAWIT (Capsicum frutescens L) PADA TINGKAT KEMATANGAN YANG BERBEDA - Angeline Y. Lapasi; Lady C. Ch. E. Lengkey; Bertje R. A. Sumayku (Universitas Sam Ratulangi, 2019)
ABSTRACTThis study aims to measure changes in moisture content, change in weight, change incolor and texture which is vacuum packed in the refrigerator to maintain the quality of cayennepepper. This study used a descriptive method, with vacuum packaging treatment at two levels ofmaturity, namely red chili and green bird's eye chilies with 3 repetitions for 17 days attemperature (6-13oC). The results showed that the initial moisture content in the vacuumpackaging of red chili peppers was 49.70% and green chili was 67.21% and the end of theobservation after 17 days in red chili was 50.70% and 82.74% in green bird's eye chilies. Thechange in weight of green chili which was vacuum packed during 17 days of storage was 0.02%.There was a change in color at the end of storage, in green bird's eye chilies, namely dark (greenyellow) and changes in red bird's eye chilies, namely dark brown (red). The texture of greenbird's eye chilies can be better preserved during 17 days of cold storage at 6-13 oC with the base5.47 mm / N, the middle 4.33 mm / N, and the tip 5.37 mm / NKeywords: Cayenne pepper, vacuum packaging, level of maturity, cold storage